HUBUNGAN MINAT BELAJAR SISWA DENGAN HASIL BELAJAR IPS SISWA KELAS V DI SD SE-GUGUS 5 KECAMATAN TAMPAN KOTA PEKANBARU - Noviana, Eddy; Antosa, Zariul (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: In the activity of teaching and learning interest is one of the main psychological factors that influence student learning process and results, because the interest is an early stage that comes within the student to produce a satisfactory values. This study aims to determine the the correlation between the student interest in study with the results in learning social studies of grade V student in se-gugus 5 primary school Tampan district Pekanbaru. Interest in learning in this study comes from the internal (inner) which includes an interest, a sense of excitement, attention, and participation. This research method is correlational with quantitative descriptive approach. The population in this research were 223 students, from the total of population of the research samples were taken as 69 students. The sampling technique used purposive sampling technique using Taro Yamane formula. The data collection was conducted by questionnaire and documentation of grade five students in social studies class from the first semester of academic year 2015/2016. The analysis technique is use the technique of analysis Product Moment. The requirements test analysis is in the form of normality and linearity test. The data were analyzed using SPSS 20. The results showed that there is a relation between the student interest in study the results in learning with social studies obtained rxy 0,421 and value tcount (3.795) > ttable (1.996) this show that there is a significant relation between the student interest in learning social studies with the results of grade V student of se-gugus 5 primary school Tampan district Pekanbaru. Interest to learn give the effect to the results of social studies that is 17,7% with a sufficient level of relation.Key Words: Interest in Learning, The Results of Learning Social Studies